ÐžÑÐ¼Ð¾Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ ÑÐ²Ð¾Ð¹ÑÑ‚Ð²Ð° ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð², Ð·Ð°Ð¼Ð¾Ñ€Ð¾Ð¶ÐµÐ½Ð½Ñ‹Ñ… Ð² ÑÑ€ÐµÐ´Ð°Ñ… Ñ Ð½ÐµÐ¿Ñ€Ð¾Ð½Ð¸ÐºÐ°ÑŽÑ‰Ð¸Ð¼Ð¸ Ð¸ Ð¿Ñ€Ð¾Ð½Ð¸ÐºÐ°ÑŽÑ‰Ð¸Ð¼Ð¸ ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð°Ð¼Ð¸ - Ramazanov, V. V.; Bondarenko, V. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
Osmotic hemolysis of erythrocytes frozen in combined crypreservatives containing polymer non-penetrating (dextran, PEG) and penetrating (DMSO, glucose) cryoprotectants was studied. Erythrocytes frozen with the polymers within the range of NaCl concentrations 0.45–0.9% are characterized by lower osmotic resistance than intact cells and by higher osmotic resistance within the range of NaCl concentrations 0.09–0.4%. The higher the polymer concentration in the freezing medium is, the higher resistance is. Combination of non-penetrating and penetrating cryoprotectants in cryopreservatives maintains normal osmotic resistance of frozen erythrocytes. The results obtained allow presuming that enhancement in osmotic resistance of erythrocytes frozen within the range of NaCl concentrations 0.09–0.4% is associated with a growth in polymer concentration gradient on cell membranes in the process of cooling. Combination a penetrating cryoprotectant with a polymer in freezing media promotes a positive correction of cryoprotective efficiency of the latter owing to weakening osmotic stress during freezing, which is caused by concentration of the non-penetrating polymer cryoprotectant.